Unplugged play. Preschool : 233 activities & games for ages 3-5 - Conner, Bobbi (Workman Publishing, 2020)
"From Animal Doctor to Lunch Bag Puppet, Letter Hunt to Life-Size Me, here are more than 200 screen-free games and activities to help kids enjoy the wholesome, old-fashioned experience of playing creatively and freely ... without technology. There are outdoor games and indoor games, games to play solo and games to play with others, arts and crafts, songs and rhymes, playdate and party favorites -- even instant activities to do at the kitchen table while dinner's cooking. All games are preschooler-tested and approved!" --